Development of resistance to insecticides in the invasive mealybug Phenacoccus solenopsis (Hemiptera: Pseudococcidae) in Pakistan. (October 2016) - Ahmad, Mushtaq; Akhtar, Shamim
Abstract: The mealybug Phenacoccus solenopsis has been a serious pest of cotton, vegetables, ornamentals and other plants since its invasion into Pakistan in 2005. Its susceptibility to commonly-used insecticides was monitored during 2005–2013 by a nymphal dip bioassay. Initially, P. solenopsis was found susceptible to a range of insecticide classes. Lethal concentration values were particularly low for organophosphates and pyrethroids. After a year of its exposure to insecticides, P. solenopsis developed moderate to high levels of resistance to pyrethroids. After two years, resistance to organophosphates methidathion and chlorpyrifos also rose to moderate to high levels. After five years of use, resistance to pyrethroids, organophosphates, neonicotinoids, endosulfan, carbosulfan, and thiocyclam was generally high to very high. Acetamiprid resistance was slow to develop, as it reached moderate level of resistance after seven years of its extensive applications. Insecticide resistance in P. solenopsis could have been managed in Pakistan if the effective and diverse insecticides were used in rotation, along with other integrated pest management tactics, at the initial stages of resistance development. Highlights: Resistance to insecticides was monitored in Phenacoccus solenopsis during 2005–2013 by a nymphal-dip bioassay. P. solenopsis developed high to very high levels of resistance to OPs, pyrethroids and neonicotinoids. Insecticide resistance in P. solenopsis could be mitigated by the rotational use of diverse chemistries.